Dad drowns, son missing in Pahang flood - FMT, Reporters (2021)
KUANTAN: The floods in Pahang claimed its first victim when a staff member of the Jerantut District Forestry Department Office drowned, while his son went missing when wading through floodwaters in Kampung Gintong, about 100km from here last night.